(untitled) (Scientific journal of the Fergana State University, 2023)
This article covers the issues of description of functional analysis in linguistics. In linguistics, an understanding of examples of functional analysis is given. Functionality, task characteristics. It studies the problems and views regarding the specific factors and the situational factor in terms of information about linguistic functions.